Battery Aging Simulation for a Fully Electric RO-RO Passenger and Vehicle Ferry - Karaosman, Mumin; Boynuegri, Ali Rifat; Eren, Yavuz (IEEE, 2024)
In recent years, advances in battery technology have accelerated the spread of electric marine vehicles. This transformation has revealed many new research topics, as marine vehicles increasingly operate on electricity. Within these research areas, it becomes clear that battery aging in electric marine vehicles is among the priority issues in terms of cost and sizing. In this context, various research studies are being carried out to understand and address the effects of battery aging. The main purpose of this research is to contribute to making electric marine vehicles more efficient, economical, and environmentally friendly. In this context, the study discussed in this article focuses on examining real-time data used by a simulation program developed with the Python programming language. Moreover, it is aimed to analyze battery aging in detail during each trip of electric ferries. This study could be a critical step toward effectively managing the energy storage systems of electric marine vehicles. The results can help develop strategies for more sustainable operation of marine vessels and guide industrial practices.
Keywords: battery aging; electrical ferry; green ship; battery size; Energy & Fuels; Engineering